Staggered Contracts and Unemployment during Recessions - Effrosyni Adamopoulou; Luis Díez-Catalán; Ernesto Villanueva (Institute of Labor Economics (IZA), 2022)
This paper studies the impact of downward wage rigidity on wage dynamics and employment flows after the outbreak of major recessions over the last 30 years in Spain. Downward wage rigidity stems from collective agreements, which set province-industry-skill specific minimum wage floors for all workers. We show that agreements signed after the onset of the 1993 and 2009 recessions settled on average for a 1.0-1.5 pp lower nominal wage growth than the agreements signed before. By exploiting variation in the renewal of collective contracts and leveraging Social Security data and the distribution of the worker-level bite of minimum wage floors, we find that in both recessions actual wage growth was indeed higher among workers covered by collective contracts signed during expansions and with wages close to the floors. However, employment responses vary across recessions. In the low-inflation recession of 2009, job losses are highly persistent and entirely driven by workers with pre-recession wages close to the minimum wage floors while in the high inflation recession of 1993, job losses were limited and short-lived. Using Labour Force Survey data in a similar setting we find that downward wage rigidity during the first year of the COVID-19 pandemic triggered adjustments at the intensive margin of labor (short time work). Our findings highlight the interplay between rigidity at different parts of the wage distribution, macroeconomic environment and labor market institutions and identify conditions under which collective contract staggering and the inability to renegotiate may amplify aggregate shocks.
Keywords: J23; J31; J50; 330; labor demand; collective bargaining; wage rigidity; staggering; minimum wages; social security data; inflation